2011
DOI: 10.3341/kjo.2011.25.6.380
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor Disruption Related to Persistent Submacular Fluid after Successful Scleral Buckle Surgery

Abstract: PurposeTo investigate serial changes in photoreceptor status and associated visual outcome in patients with persistent submacular fluid after successful scleral buckle surgery for macula-off rhegmatogenous retinal detachment.MethodsThis was a prospective observational case series including 76 consecutive patients who underwent successful scleral buckle surgery for macula-off rhegmatogenous retinal detachment with symptom duration ≤90 days at a single tertiary hospital. Optical coherence tomography (OCT) and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…28 The effect of ELM disruption was highlighted in the present study by its relationship with higher IT values of the P1 response and was consistent with the fact that IT P1 is known to be a very sensitive measurement of outer retinal function. 19 Subretinal edema fluid was observed in 18% of eyes at M1 and for the most part resolved at M12 (3%), consistent with previously reported frequencies: from 10% to 81% of cases at M1 25,[29][30][31] resolved in 4% to 33% of the cases at 6 months. 17,27,30,31 The strengths of this study include its prospective design, the relatively high number of patients, the long duration of follow-up, and the use of an objective technique for visual function such as mfERG.…”
Section: Discussionsupporting
confidence: 90%
“…28 The effect of ELM disruption was highlighted in the present study by its relationship with higher IT values of the P1 response and was consistent with the fact that IT P1 is known to be a very sensitive measurement of outer retinal function. 19 Subretinal edema fluid was observed in 18% of eyes at M1 and for the most part resolved at M12 (3%), consistent with previously reported frequencies: from 10% to 81% of cases at M1 25,[29][30][31] resolved in 4% to 33% of the cases at 6 months. 17,27,30,31 The strengths of this study include its prospective design, the relatively high number of patients, the long duration of follow-up, and the use of an objective technique for visual function such as mfERG.…”
Section: Discussionsupporting
confidence: 90%
“…Chan et al found that images with high signal density in CSC were accompanied by the dilatation of large blood vessels, suggesting that the choroidal thickening in CSC may be due to the expansion of blood vessels [33]. Therefore, it was suggested [34,35] that the mechanism of SR after SB surgery may be similar to the pathogenesis of CSC, such as choroidal hypertonicity and choroidal thickening. The results of our study show a moderate positive correlation between SRFH and SFCT at the macular fovea (r s = 0.462, P = 0.000).…”
Section: Discussionmentioning
confidence: 99%
“…In a few cases, intravitreal triamcinolone was also tried 7. One school of thought advocates for early management since SRF can cause permanent damage to photoreceptors if left untreated 10–12. In contrast, a recent study8 found no significant difference in patients’ visual recovery with or without surgical intervention.…”
Section: Discussionmentioning
confidence: 99%